The Role of Compensation on Leadership Style and Job Satisfaction - Pradiptya, Adhi; Prabasari, Bonita; Dewi Endah Amaliyah, Erlina (Economics and Business Solutions Journal, 2025)
Job satisfaction is an important factor in employee performance and productivity, so it needs a leader who is able to direct and motivate in order to increase employee job satisfaction. This study aims to examine the effect of leadership style on job satisfaction with compensation as a mediating variable. This research was conducted on employees of PT Asuransi Raksa Pratikara, with a total of 84 respondents involved. This research used primary data collected through questionnaires distributed to employees. This type of research is quantitative research with the analysis method using SEM-PLS with the help of the SmartPLS 3 program. The results of this study indicate that leadership style had a significant effect on job satisfaction and compensation. Likewise, compensation had a significant effect on job satisfaction. Thus, it is proven that compensation is able to mediate the effect of leadership style on job satisfaction